New citrinin analogues produced by coculture of the marine algal-derived endophytic fungal strains Aspergillus sydowii EN-534 and Penicillium citrinum EN-535. (June 2018) - Yang, Sui-Qun; Li, Xiao-Ming; Li, Xin; Li, Hong-Lei; Meng, Ling-Hong; Wang, Bin-Gui
Graphical abstract: Highlights: Fungal strains Aspergillus sydowii and Penicillium citrinum were cocultured. A new citrinin dimer and a new citrinin monomer along with eight analogs were isolated. Several compounds showed antimicrobial and anti-influenza neuraminidase activities. Abstract: Ten citrinin analogues (1 –10 ), including a new citrinin dimer ( seco- penicitrinol A, 2 ) and a new citrinin monomer (penicitrinol L, 3 ), were isolated from the EtOAc extracts of the coculture of two marine algal-derived endophytic fungal strains Aspergillus sydowii EN-534 and Penicillium citrinum EN-535. Their structures were elucidated by detailed analysis of their NMR spectra, ECDs, HRESIMS, optical rotation, and X-ray crystallographic data, and by comparison with literature data as well. The crystal structure of compound1 was reported for the first time in this paper and resulted in unambiguous confirmation of its absolute configuration as 3 R, 4 S, 2′ R, and 3′ S, while the absolute configuration of compound3 was determined by TDDFT calculations of its ECD spectrum. The antimicrobial and influenza neuraminidase inhibitory activities of compounds1 –10 were evaluated.